PERLINDUNGAN HUKUM TERHADAP MASYARAKAT DALAM PELAYANAN ADMINISTRASI KEPENDUDUKAN - Badria Khazanah Teang Faisal; Siti Kotijah; Agustina Wati (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research discusses the Legal Protection for the Community in Population Administration Services. However, population administration services are misused with the use of brokers by the community. This research uses a social legal approach. The inhibiting factors in legal protection for the community of Sumber Sari Village, Long Mesangat District, Kutai Timur Regency, in population administration services, are complex bureaucracy, lack of knowledge and development of low human resources about law, and limited access. Legal protection for the community in population administration services is very important to ensure that the rights of the Sumber Sari Village community are fulfilled and protected.